Industry Tax Planning and Stock Returns - Heitzman, Shane M.; Ogneva, Maria (The Accounting Review, 2019)
ABSTRACT We find evidence that equity returns increase with the propensity for tax planning in a firm's industry. This risk premium is imposed on all firms in the industry, even those that are less aggressive than their peers. The industry-based risk premium coexists with a firm-specific discount associated with active tax planning strategies that carry low systematic risk. The discount on tax planning at the firm level, however, is dwarfed by the premium on tax planning at the industry level, and is concentrated in industries that are less likely to attract scrutiny from the tax authority.